Avaliação da força e da coativação entre extensores e flexores do punho durante atividades funcionais em sujeitos com osteoartrite de mão - Tossini, Natália Barbosa (2018)
Introduction: Grip strength in subjects with hand osteoarthritis (OA) is lower when compared to healthy individuals. However, to date, grip strength has been assessed only in subjects with advanced OAM. In addition, during activities involving the use of pinch and/or the grip of objects, it is necessary that the wrist extensor muscles act to stabilize this joint, and no study has evaluated this muscle group in subjects with OAM in the early stages of the disease. Objectives: The objective of this dissertation was to evaluate the maximum grip strength, self-reported function, magnitude of activation and coactivation between the extensor and flexor muscles of the wrist in subjects with initial degrees of OAM and to compare with healthy subjects. In addition, it was aimed correlate grip strength and flexor and extensor strength of the wrist with the self-reported function, pain and stiffness in subjects with OAM in the early stages of the disease. Methods: 32 subjects, divided into two groups: GC (n = 16, 55±7,42, healthy subjects) and GOAM (n = 16, 57±7,82, subjects with hand OA, grades II and III) participated in this study. All participants responded to an initial assessment form and the Australian / Canadian Hand Osteoarthritis Index (AUSCAN) and Disabilities of the Arm, Shoulder, and Hand (DASH) questionnaires. After that, evaluation of the grip strength and the flexor and extensor isometric flexor torque were performed. The electrical signal evaluation of ulnar flexor carpi ulnaris (FCU), flexor digitorum superficialis (FDS) and extensor (EXT) muscles was performed during functional activities (cutting with scissors, writing and opening and closing a bottle), and concomitant with the grip test. The groups were compared using the Student's t-test for independent samples or Mann-Whitney. Also, the Person's correlation was applied to the variables of interest (p≤0.05). Results: For the mean activation of the flexor and extensor muscles of the wrist, there was a lower muscular activation in GOAM in all activities performed, with statistical difference for FDS (p = 0.01) and EXT (p = 0.04) in scissors task and FCU in the task of the bottle (p = 0,05). No difference was found between the groups for the index of coactivation nor for the grip strength. A moderate and negative correlation was found between the grip strength and the DASH questionnaire (r =-0.59, p = 0.01), as well with the AUSCAN questionnaire (r =-0.66, p≤0, 01). No correlations were found between the flexor and extensor isometric torques with the questionnaires. Conclusion: People with hand OA, already in the early stages of the disease, have less activation of the wrist muscles during the execution of some functional tasks, which may be related to a muscle inhibition. In addition, at the beginning of the disease grip strength correlates with functional alterations, pain and self-reported stiffness.